Rehabilitation Programs in Prison: Helping the Self wounded to Heal - Poudel, Prativa (Literary Studies, 2023)
Rehabilitation of prison inmates is a major discourse these days. The situation of rehabilitation services for the improvement of criminals in prison is a major issue among academics, counselors, educators, psychologists, security personnel, legal practitioners, medical doctors, and so on in recent times. Our society has some kind of preconception about ex-criminals, which is mostly negative and hostile, and the stigma and labeling attached to them can hardly be erased. And this is not only limited to ex-criminals but also their family members and even the next generation as well. This makes social adjustment difficult for the ex-criminals. On the other hand, after serving a fixed term in jail, ex-criminals carry the prison trauma that hunts them back again and again even after they try to lead their normal life in society. They reflect back on their criminal activities and the harsh treatment meted out to them in prison. This makes it difficult to adjust to mainstream society, and the chance of repeat offenses becomes high. Jails are not to be taken as a means of torturing the offenders; instead, they should be called penitentiaries where the prisoners are treated compassionately so they would not feel degenerated and get some chances to reform themselves. If rehabilitation programs conducted in prisons are the central part of truly reforming the inmates, they can live crime-free life after they are released from prison. These reformative programs will have to be aimed at changing the lives of inmates so that they can restart life with self-respect and confidence. This paper explores the present system of Central Jail (NAKHU JAIL), need and importance of rehabilitation programs, the challenges faced by them, and methods to enhance their effectiveness.